Upaya Meningkatkan Akurasi Passing Dengan Latihan Triangle dan Small Sided Games Pada Ssb Pespa Pabedilan Kidul - Zaenudin, Mohammad; Adityatama, Firman; Nur, Hana Astria (Journal of Physical Education and Sport Science, 2025)
Mohammad Zaenudin (NIM 182223076) (2022) with the title "Efforts to Improve Passing Accuracy with Triangle Exercises and Small Sided Games at SSB Pespa Pabedilan Kidul". This study aims to determine whether the triangle and small side game exercises affect the accuracy of passing, to find out how much the triangle and small sided game exercises affect the accuracy of passing. The method used in this research is the experimental method. The sampling technique used saturated sampling technique with a total of 20 students, namely group A 10 students and group B 10 students who became the sample. The instrument in this study was a passing test. The data analysis techniques in this study were normality test, homogeneity test, hypothesis testing and determination test which were used to determine the effect and how big the triangle and small sided games were on increasing the accuracy of passing SSB Pespa Pabedilan Kidul. From the test results using the SPSS V.16.0 program, the values ​​for the normality test and homogeneity test are greater than 0.05, which means the data is normally distributed and homogeneous. In the paired sample T test, a value of 0.000 is obtained, which means that Ha is accepted and Ho is rejected, thus there is an effect of triangle training and small sided games on the accuracy of passing. In the determination test, the triangle value is 76.4% while the small sided games value is 26.2%, which means that the triangle exercise is more influential than the small sided games exercise.